2000
DOI: 10.1046/j.1364-3703.2000.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory element involved in rapid activation of parsley ELI7 gene family members by fungal elicitor or pathogen infection

Abstract: In parsley (Petroselinum crispum), members of the ELI7 gene family were rapidly transcriptionally activated following treatment with an elicitor derived from the phytopathogen Phytophthora sojae. Several cDNA and genomic ELI7 clones were isolated. The deduced amino acid sequences revealed close similarity to fatty acid desaturases/hydroxylases, however, the precise functions are still unknown. Analysis of the promoters of two strongly elicitor-induced family members, ELI7.1 and ELI7.2, allowed us to functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…A similar element has been reported to direct jasmonate and elicitor-responsive expression (JERE; AGACCGCC) (Menke et al, 1999), and another (DRE; TACCGAC) directs cold-, salt stress-, and dehydration-responsive expression (Yamaguchi-Shinozaki and Shinozaki, 1994). Recently, another similar GCC-like element called box S (AGCCACC) has been identified that directs expression by fungal elicitors (Kirsch et al, 2000). It appears that minor variations in the core sequences impart responsiveness to different stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar element has been reported to direct jasmonate and elicitor-responsive expression (JERE; AGACCGCC) (Menke et al, 1999), and another (DRE; TACCGAC) directs cold-, salt stress-, and dehydration-responsive expression (Yamaguchi-Shinozaki and Shinozaki, 1994). Recently, another similar GCC-like element called box S (AGCCACC) has been identified that directs expression by fungal elicitors (Kirsch et al, 2000). It appears that minor variations in the core sequences impart responsiveness to different stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Because it was unknown whether any of the elements were functional in planta, we used tetramers in initial experiments to ensure that any expression would be strong enough to be detectable by ␤ -glucuronidase (GUS) staining. The first elements tested were boxes W1 and W2 from the parsley PR1 genes (Rushton et al, 1996), box S from the parsley ELI7 genes (Kirsch et al, 2000), a novel element called box D from the parsley PR2 gene (P.J. Rushton and K. Hahlbrock, unpublished results), and an element we termed the Gst1 box from the potato gst1 gene (Strittmatter et al, 1996).…”
Section: Elicitor-inducible Synthetic Promotersmentioning
confidence: 99%
“…In addition to ELI12, a functionally characterized acetylenase from Sclerotinia sclerotiorum-challenged Helianthus annuus (sunflower) flower heads was cloned and other instances of viral-induced diverged FAD2s are known from Solanaceae species [104,105]. Other pathogen-responsive P. crispum genes likely to be acetylenases have a novel cis-regulatory element and are not upregulated in response to wounding, jasmonate, ultraviolet light, or ethylene [106]. How acetylenic secondary metabolism is integrated into pathogen response and understanding the selectivity of the defensive mechanism still poses many interesting questions.…”
Section: Cloning and Expression Of The Lipid-desaturating Components Ofmentioning
confidence: 99%
“…Then JERE was reported to modulate the expressions of both elicitorand jasmonate-responsive genes (Menke et al, 1999); GCC box, an ethylene-responsive element, was identified in the promoters of both ethylene signaling pathway genes and pathogen-related genes (OhmeTakagi et al, 2000). More recently, S box, a GCC-like element, was shown to be responsible for the activation of fungal elicitors-triggered gene expression (Kirsch et al, 2000;Rushton et al, 2002); HSRE, an HSR203 responsive element, was located in the promoter region of HSR203J to mediate the hypersensitive response (HR) in Nicotiana tabacum (Pontier et al, 2001).…”
Section: Introductionmentioning
confidence: 99%